Improving Sales Performance Of A Penang Based Car Coating Company - Lim, Shing Yeu (2014)
Sierra Glow Penang, newly established Penang based car coating company is facing the challenge of low number of customers that has led to low sales performance of business. The co-founder, Mr Woo worry that if this trend persists, he would not be able to sustain his business. This case explore the reasons for why this happened and what can be done to improve the situation. An analysis of industry background and company background was carried out to identify the internal and external environment and issues facing the company. Case analysis was done through Porter’s Five Forces, Fishbone analysis, SWOT and TOWS matrix analysis. In order to gain insights on the issue, interviews were conducted with co-founders, competitors and customers.